KAJIAN ANALISIS URIN BAYI PEREMPUAN DAN LAKI LAKI DENGAN COMPUTED RADIOGRAPHY - MAIYENA, SRI (IAIN Batusangkar, 2014)
This study aimed to see whether there are differences in the profile line image and the linear attenuation coefficient in the urine baby boys and baby girls who drink only breast milk alone and additional milk with computed radiography, and relation to differences in impurity law. The study was conducted in the x-ray radiology Hospital National Stroke Bukittinggi. The study sample consisted of urine male and female babies who drink only breast milk and urine only baby girls and boys who drank ation and additional milk. CR image retrieval is performed three days (22, 25 and 26 September 2014) with a voltage variation of 50 and 60 kV and 100 mA using a strong current and exposure time of 5 ms. The image was analyzed visually, and physical image quality. The results showed that visual image acquisition of the third day and with two different voltage variations indicate that there are differences in the brightness, contrast and sharpness of the image. Analysis of image quality (based grafi line profile image) shows the pattern of the same line profile image on the third day of taking images at a voltage of 60 kV. Physical Analysis of the image showed that the urine samples tested had a pattern of linear attenuation coefficient value equal to the voltage of 60 kV on three different days. Linear attenuation coefficient values greatest U1 and U3 linear attenuation coefficient on the third day of the smallest image retrieval. The big difference in the value of the significant linear attenuation coefficient between U1 and U3 sample is related to differences in the urine purification unclean baby boys and baby girls.Key words: baby boy urine, urine baby girl, computed radiography, law unclean in Islam